2018
DOI: 10.1111/imm.12886
|View full text |Cite
|
Sign up to set email alerts
|

P21‐activated kinase 2 is essential in maintenance of peripheral Foxp3+ regulatory T cells

Abstract: SummaryThe p21‐activated kinase 2 (Pak2), an effector molecule of the Rho family GTPases Rac and Cdc42, regulates diverse functions of T cells. Previously, we showed that Pak2 is required for development and maturation of T cells in the thymus, including thymus‐derived regulatory T (Treg) cells. However, whether Pak2 is required for the functions of various subsets of peripheral T cells, such as naive CD4 and helper T‐cell subsets including Foxp3+ Treg cells, is unknown. To determine the role of Pak2 in CD4 T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…119 Ectopic FOXP3 expression inhibits almost all tumor cell types despite the lack of analogous research with the two known X-linked tumor suppressors. [120][121][122][123] Recent anisomycin studies have shown that FOXP3 expression in mice and human tumor cells is therapeutic. 114 Carcinogenesis often involves TSG dysfunction.…”
Section: Targeted Therapies For Tumors Through Restoration Of Activit...mentioning
confidence: 99%
See 1 more Smart Citation
“…119 Ectopic FOXP3 expression inhibits almost all tumor cell types despite the lack of analogous research with the two known X-linked tumor suppressors. [120][121][122][123] Recent anisomycin studies have shown that FOXP3 expression in mice and human tumor cells is therapeutic. 114 Carcinogenesis often involves TSG dysfunction.…”
Section: Targeted Therapies For Tumors Through Restoration Of Activit...mentioning
confidence: 99%
“…Elegant investigations showed that tumors can become “addicted” to Trp53 (p53) depletion 119 . Ectopic FOXP3 expression inhibits almost all tumor cell types despite the lack of analogous research with the two known X‐linked tumor suppressors 120–123 . Recent anisomycin studies have shown that FOXP3 expression in mice and human tumor cells is therapeutic 114 .…”
Section: Tsgs X‐linked Tsgs and Their Involvement In Cancersmentioning
confidence: 99%